Ditransitives in Swedish. A Usage-Based Study of the Double Object Construction and Semantically Equivalent Prepositional Object Constructions 1800–2016 - Ditransitives in Swedish. The whole dataset - Valdeson, Fredrik (Stockholm University, 2021)
The study examines the use of the Swedish double object construction (the DOC) and compares this with three semantically equivalent prepositional object constructions (POCs): the till-POC, the åt-POC and the för-POC. The study has a diachronic perspective, investigating changes in the use of these four constructions between 1800 and 2016. The data were collected from the National Language Bank of Sweden (Nationella Språkbanken). More specifically, the data are from the corpora listed below.

Svensk prosafiktion https://spraakbanken.gu.se/resurser/spf
Bonniersromaner 1976–77 https://spraakbanken.gu.se/resurser/romi
Bonniersromaner 1980–81 https://spraakbanken.gu.se/resurser/romii
Norstedtsromaner 1999 https://spraakbanken.gu.se/resurser/rom99
Bloggmix 2016. https://spraakbanken.gu.se/resurser/bloggmix2016

The data set contains examples of the Swedish double object construction (e.g. "ge ngn ngt" 'give sb. sth.', "visa ngn ngt" 'show sb. sth.') and semantically equivalent prepositional object constructions with the prepositions "till" (e.g. "ge ngt till ngn" 'give sth. to sb.'), "åt" (e.g. "ge ngt åt ngn" 'give sth. to sb.') and "för" (e.g. "visa ngt för ngn" 'show sth. to sb.'). The examples were collected from the corpora Svensk prosafiktion, Bonniersromaner I, Bonniersromaner II, Norstedtsromaner and Bloggmix 2016 (see the general description in Section 2). See Valdeson (2021) for a full account of the principles of data collection.

Studien undersöker bruket av svenskans dubbelobjektskonstruktion (DOK) och jämför detta med tre semantiskt likvärdiga prepositionsobjektskonstruktioner (POK:ar): till-POK:en, åt-POK:en och för-POK:en. Studien har ett diakront perspektiv, med fokus på förändringar i bruket av de fyra konstruktionerna mellan åren 1800 och 2016. Materialet är insamlat från Nationella Språkbanken, närmare bestämt från de korpusar som listas nedan.

Svensk prosafiktion https://spraakbanken.gu.se/resurser/spf
Bonniersromaner 1976–77 https://spraakbanken.gu.se/resurser/romi
Bonniersromaner 1980–81 https://spraakbanken.gu.se/resurser/romii
Norstedtsromaner 1999 https://spraakbanken.gu.se/resurser/rom99
Bloggmix 2016. https://spraakbanken.gu.se/resurser/bloggmix2016

Datasetet innehåller belägg på svenskans dubbelobjektskonstruktion (t.ex. "ge ngn ngt", "visa ngn ngt") och semantiskt likvärdiga prepositionsobjektskonstruktioner med prepositionerna "till" (t.ex. "ge ngt till ngn"), "åt" (t.ex. "ge ngt åt ngn") och "för" (t.ex. "visa ngt för ngn"). Beläggen är hämtade från korpusarna Svensk prosafiktion, Bonniersromaner I, Bonniersromaner II, Norstedtsromaner och Bloggmix 2016 (se den allmänna beskrivningen i sektion 2). Se Valdeson (2021) för fullständig beskrivning av principerna för materialinsamlingen.
Bitransitiver i svenskan. En bruksbaserad studie av dubbelobjektskonstruktionen och semantiskt likvärdiga prepositionsobjektskonstruktioner 1800–2016 - Bitransitiver i svenskan. Hela datasamlingen
Keywords: Linguistics; Språkvetenskap; historical linguistics; språkhistoria; corpus data; korpusdata; Swedish; svenska; Language and linguistics; Språk och lingvistik; Comparative Language Studies and Linguistics; Jämförande språkvetenskap och allmän lingvistik; Studies of Specific Languages; Studier av enskilda språk